Nurse-Driven Catheter-Associated Urinary Tract Infection Reduction Process and Protocol: Development Through an Academic-Practice Partnership. Issue 4 (October 2016) - Johnson, Pamela; Gilman, Anna; Lintner, Alicia; Buckner, Ellen
Abstract : Translating evidence-based practices to the bedside can be facilitated by an active academic-practice partnership between nursing faculty and frontline nursing staff. A collaborative effort between the university's academic nurses and the medical center's clinical nurses explored, created, implemented, and evaluated an evidence-based nurse-driven protocol for decreasing the rate of catheter-associated urinary tract infections. The nurse-driven protocol was piloted in 4 intensive care units and included nurse-driven orders for catheter discontinuation, utilization of smaller bore urinary catheters, addition of silver-based cleansing products for urinary catheter care, and education of staff on routine catheter care and maintenance. Data were collected for more than 8 months pre- and postimplementation of the nurse-driven protocol. Postimplementation data revealed a 28% reduction in catheter-associated urinary tract infections in the intensive care units as compared with preimplementation. Secondary benefits of this academic-practice partnership included strengthening the legitimacy of classroom content as lessons learned were integrated into courses in the nursing curriculum. The result of the partnership was a stronger sense of collaboration and collegiality between hospital staff and the university faculty. Transformative leadership engaged numerous stakeholders through collaborative efforts to realize best practices. An academic-practice partnership facilitates transformative change and provides structural stability and sustainability.